MRI-targeted or standard biopsy for prostate-cancer diagnosis - Kasivisvanathan, Veeru; Hadaschik, Boris (The New England journal of medicine, 2018)
Multiparametric magnetic resonance imaging (MRI), with or without targeted biopsy, is an alternative to standard transrectal ultrasonography-guided biopsy for prostate-cancer detection in men with a raised prostate-specific antigen level who have not undergone biopsy. However, comparative evidence is limited.